Development of Human Resources, Competence, and Supervision of the Performance of Clinical Nursing Staff in Hospitals - Adref, Ferry; Mattalatta; Malik, Tajuddin (Cendekiawan Indonesia Timur, 2023)
As one of the healthcare facilities, the hospital has a very strategic role in accelerating the improvement of the health status of the Indonesian people. Human resource development policies are guidelines or activities carried out by organizations or agencies to develop or increase work professionalism, such as knowledge and skills improvement programs. This research is qualitative research according to the object of this study, so this type of research is included in the category of library research. Data collection techniques include identifying books, papers, articles, magazines, websites, or other information related to this study. The data analysis technique uses the Miles and Huberman model, namely qualitative analysis activities are carried out interactively and continuously until it is deemed sufficient. The study results indicate that nursing is a form of health service that is professional in meeting basic human needs that can be addressed by individuals, families, or communities in the healthy-sick range. Supervision in the context of nursing is a process of providing support for the resources nurses need to complete tasks to achieve the goals that have been set.